PENGARUH KUALITAS PELAYANAN DAN SUASANA TOKO TERHADAP MINAT BELI ULANG MELALUI KEPUASAN KONSUMEN PADA MEULIGOE KUPI ATJEH BINJAI - Rizaldi, Tri; Hutasuhut, Saidun (Relawan Jurnal Indonesia, 2024)
The level of interest in repurchasing MKA from pre-research results is around 39.2%, which is quite low. The aim of this research is to find out how customer satisfaction influences repurchase interest at Meuligoe Kupi Atjeh in relation to service quality and store atmosphere. This research uses a causal associative method with a quantitative approach. Using the accidental sampling method, questionnaires were distributed to 100 MKA customers to collect data. Path analysis and bootstrapping were used to analyze the data to determine whether customer satisfaction acts as a mediator. The research results found that service quality and store atmosphere have a significant effect on customer satisfaction. Repurchase intention is positively and significantly influenced by store atmosphere, service quality and customer satisfaction. Consumer satisfaction is proven to be a mediator of the impact of service quality and store atmosphere on repurchase intention. The implications of this research indicate that further development of service quality and store atmosphere can increase consumer satisfaction, thereby stimulating repeat purchase interest. These findings provide a practical contribution to MKA's management strategy to increase consumers' repurchase interest by managing the store atmosphere and improving service quality.